2011
DOI: 10.1017/s136898001100276x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic differences in adolescents’ breakfast eating, fruit and vegetable consumption and physical activity in Ghana

Abstract: Objective: Few studies have investigated the association between adolescents' socio-economic status (SES) and health behaviours in developing countries. Socio-economic differences in breakfast eating, fruit and vegetable consumption and physical activity were investigated among Ghanaian adolescents. Design: A school-based survey of 12-18-year-olds (n 1195, response rate 89?7 %) was conducted in 2008. Logistic regression analyses were applied to study the associations between breakfast eating, fruit and vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
72
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 25 publications
(48 reference statements)
16
72
1
1
Order By: Relevance
“…In line with previous studies, the results showed significant gender differences in physical activity and eating behaviour combined, with boys more likely to engage in physical activity than girls (20,24), and girls also more likely to engage in healthy eating behaviour than boys (25). Social pressure and individual's sense of body image on the part of girls may also explain why girls were more likely to engage in healthy eating behaviour than boys.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies, the results showed significant gender differences in physical activity and eating behaviour combined, with boys more likely to engage in physical activity than girls (20,24), and girls also more likely to engage in healthy eating behaviour than boys (25). Social pressure and individual's sense of body image on the part of girls may also explain why girls were more likely to engage in healthy eating behaviour than boys.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with that of previous research studies that have found that higher socioeconomic groups have healthier diets because they may have higher educational levels and may be more health conscious and have healthier lifestyles including eating behaviour (e.g. higher intakes of fruit, lean meat, oily fish, wholemeal products, and raw vegetables) (16,20,36 In spite of the potential contributions of this study, there are some limitations that must be noted. Although the sample consists of Senior High School adolescents, it only comprised of second-year and third-year students thereby diminishing the ability to generalise the findings to all Senior High School students across Ghana.…”
Section: Parental Education and Eating Behavioursupporting
confidence: 92%
See 1 more Smart Citation
“…[29][30][31][32][33][34][35] In addition, skipping breakfast has been associated with poor nutritional status, increased body adiposity and risk of chronic diseases. 2,36,37 The results are in agreement with earlier researchers [38][39][40] who reported that adolescents from affluent families had better quality breakfast than those belonging to the lower socioeconomic group and that skipping breakfast unhealthy dietary practices were more prevalent among adolescent girls.…”
Section: Discussionsupporting
confidence: 84%
“…A possible explanation for this relationship could be due to the fact that students who use Facebook excessively stay online late into the night and may get up too late and therefore likely to skip breakfast before classes. Again in Ghana, it is estimated that about 52% of the populations are below the poverty line, and therefore less likely to be concerned about breakfast, as planning what and when to eat could be considered as luxury (Doku, Koivusilta, Raisamo, & Rimpelä, 2013). It is however, important for health interventions to address the high rate of skipping breakfast reported in this study as regular intake of breakfast increases the possibility of a balanced diet and improves overall nutritional status and nutritional density, particularly during the early phases of life ( Nicklas, O'Niel, & Meyers, 2004).…”
Section: Discussionmentioning
confidence: 99%